Section 6: Education and Consumer Informatics: Education and Consumer Health Informatics - Mantas, J. (Yearbook of Medical Informatics, 2007)
To report on recent efforts in the field of consumer health informatics (CHI) and education.A review of the literature we selected on using search engines and Medline with terms from consumer health informatics and education. Twenty two articles match these criteria.A great diversity of work spans the field of CHI. This relatively new field now faces challenges due to rapidly advancing technologies and the increasing empowerment of citizens connected over the worldwide web.The benefits of enhancing CIH components within existing medical curricula are already being noted.. Additionally, updated recommendations on health and medical informatics should incorporate CHI.Geissbuhler A, Haux R, Kulikowski C, editors. IMIA Yearbook of Medical Informatics 2007.
Keywords: Health informatics; medical informatics; consumer health informatics; education